ASPECTS OF THE ECOLOGY OF PHLEBOTOMINES (Diptera: Psychodidae: Phlebotominae) IN AN AREA OF CUTANEOUS LEISHMANIASIS OCCURRENCE, MUNICIPALITY OF ANGRA DOS REIS, COAST OF RIO DE JANEIRO STATE, BRAZIL - Aguiar, Gustavo Marins de; Azevedo, Alfredo Carlos Rodrigues de; Medeiros, Wagner Muniz de; Alves, Joao Ricardo Carreira; Rendeiro, Vanessa (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Over a complete two-year period, phlebotomine specimens were caught in an area of cutaneous leishmaniasis occurrence in the municipality of Angra dos Reis. A manual suction tube was used to catch phlebotomines on house walls, and also light traps in domestic and peridomestic settings and in the forest. This yielded 14,170 specimens of 13 species: two in the genus Brumptomyia and eleven in the genus Lutzomyia. L. intermedia predominantly in domestic and peridomestic settings, with little presence in the forest, with the same trend being found in relation to L. migonei, thus proving that these species have adapted to the human environment. L. fischeri appeared to be eclectic regarding location, but was seen to be proportionally more endophilic. L. intermedia and L. migonei were more numerous in peridomestic settings, throughout the year, while L. fischeri was more numerous in domestic settings except in March, April, May and September. From the prevalence of L. intermedia, its proven anthropophily and findings of this species naturally infected with Leishmania (Viannia) braziliensis, it can be incriminated as the main vector for this agent of cutaneous leishmaniasis in the study area, especially in the peridomestic environment. L. fischeri may be a coadjuvant in carrying the parasite.